ANALISIS KINERJA SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN TEMPAT HIBURAN KARAOKE DI KOTA PEKANBARU - Edelnasya Mulanatara; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Karaoke Bar in Pekanbaru is currently growing very rapidly. Karaoke is a place of entertainment that provides places, equipment, and facilities to sing along with music. With the rapid development of karaoke bar can have a negative impact. So it is necessary to disciplining the karaoke bar that violates. The problem of this research is how the performance of Civil Service Police in disciplining karaoke bar in Pekanbaru and what the factors are affecting the performance of Civil Service Police in disciplining karaoke bar in Pekanbaru.The concept of theory that researchers use is organization and performance. This research type is qualitative research with descriptive method. The selection of informants of this research using purposive sampling technique, which this informant has been predetermined and the determination of informants based on the consideration that the informants selected are the people who know and involved. Data collection techniques through interviews, documentation and observation.The results of this study, the performance of the Civil Service Police Pekanbaru in disciplining karaoke bar votes yet. By looking at the many karaoke bar that violates the content Provisions of Regulation Number 3 Year 2002 of public entertainment, still finding a karaoke bar open over 10 hours a night even until the early hours, selling liqour, became a place of gambling and place of drug use. The factors that affect the performance of the Civil Service Police in Pekanbaru to disciplining karaoke bar is the lack of number of personeel, equipment or facilities have been inadequate as well as the Backing which affect the implementation of disciplining karaoke bar in Pekanbaru.Keywords: Disciplining, Performance, Organization, Karaoke